1999
DOI: 10.1089/end.1999.13.221
|View full text |Cite
|
Sign up to set email alerts
|

Metal Mesh Stents for Ureteral Obstruction Caused by Hormone-Resistant Carcinoma of Prostate

Abstract: Metal mesh ureteral stents give poor palliation in distal strictures caused by hormone-refractory carcinoma of the prostate. Permanent nephrostomy may be a more acceptable alternative in these patients with short life expectancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In vitro studies with poly(ethylene oxide)/polyurethane composite hydrogel (Aquavene) showed promising results, with superior resistance to encrustation and intraluminal blockage over 24 weeks [18]. Other materials used recently as permanently implanted stents for relieving malignant obstructions and ureteral strictures are metallic, super-alloy, titanium or nickel/titanium stents designed to be covered by normal urothelium [1,29,40,42]. However, the extent to which epithelialization takes place remains to be seen.…”
Section: Urological Biomaterials and Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with poly(ethylene oxide)/polyurethane composite hydrogel (Aquavene) showed promising results, with superior resistance to encrustation and intraluminal blockage over 24 weeks [18]. Other materials used recently as permanently implanted stents for relieving malignant obstructions and ureteral strictures are metallic, super-alloy, titanium or nickel/titanium stents designed to be covered by normal urothelium [1,29,40,42]. However, the extent to which epithelialization takes place remains to be seen.…”
Section: Urological Biomaterials and Biocompatibilitymentioning
confidence: 99%
“…In the last few years, several clinical studies have focused on assessment of new implantable stents, which are expandable and permanent [1,29,30,40,42]. Time will tell if these can remain in the host without becoming a nidus for infections, encrustation, toxicity, and other adverse eects.…”
Section: Design Shape And¯ow Studiesmentioning
confidence: 99%
“…4 The maintenance of its patency is crucial for success, but high early failure rates have been reported and reach up to 58%. 1,8,13 Factors related to stent failure have been described and include stent encrustation and luminal obstruction caused by debris and mucus. 8 Also, since open flow dynamics predominates in this setting, failure to maintain cross-sectional stability leads to a decrease in urine flow.…”
Section: Discussionmentioning
confidence: 99%
“…1 Urinary drainage in this setting was first described by Gibbons et al 2 in 1976. Whether or not to perform urinary drainage should be an individualized decision 1 and can be executed percutaneously with the use of a nephrostomy tube or through endoscopic transurethral retrograde placement of a ureteral stent.…”
Section: Introductionmentioning
confidence: 99%
“…Many metallic ureteric stents have been developed to overcome the limitations of conventional PCN or double-J stents. Previously developed ureteric uncovered metallic mesh stents tend to be easily obstructed by urothelial hyperplasia or tumor ingrowth [4,5]. Available metallic ureteric stents include Allium® URS, Memokath™-051, Resonance®, and Uventa™.…”
Section: Introductionmentioning
confidence: 99%